2020
DOI: 10.1038/s41598-020-66358-2
|View full text |Cite
|
Sign up to set email alerts
|

Ergot alkaloid mycotoxins: physiological effects, metabolism and distribution of the residual toxin in mice

Abstract: The complex ergot alkaloids, ergovaline and ergotamine, cause dysregulation of physiological functions, characterised by vasoconstriction as well as thermoregulatory and cardiovascular effects in grazing livestock. To assess the effect of the mycotoxins, blood pressure and heart rate of male mice were measured, and metabolite profiling undertaken to determine relative abundances of both ergotamine and its metabolic products in body and brain tissue. Ergotamine showed similar cardiovascular effects to ergovalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 41 publications
5
27
0
1
Order By: Relevance
“…Thus, producing a multitude of effects depending on the secondary structure. The ergopeptines ergotamine and ergovaline have similar activities in mice models [ 47 ] causing vasoconstriction, increase in blood pressure and bradycardiac properties. Epichloe festuca var lolii has been studied with respect to its particular ergovaline pathway [ 48 ], this analysis was for a standard toxic strain that follows the published pathway to produce a ‘standard’ level of ergovaline.…”
Section: Ergot Alkaloid Profiles Produced In Epichloe Endophytesmentioning
confidence: 99%
“…Thus, producing a multitude of effects depending on the secondary structure. The ergopeptines ergotamine and ergovaline have similar activities in mice models [ 47 ] causing vasoconstriction, increase in blood pressure and bradycardiac properties. Epichloe festuca var lolii has been studied with respect to its particular ergovaline pathway [ 48 ], this analysis was for a standard toxic strain that follows the published pathway to produce a ‘standard’ level of ergovaline.…”
Section: Ergot Alkaloid Profiles Produced In Epichloe Endophytesmentioning
confidence: 99%
“…Kallenbach [ 2 ] estimates that about 12 million beef cows graze tall fescue in this region with reproductivea and liveweight losses estimated at USD 267 per cow in 2015. Most tall fescue contains an endophyte ( Epichloë coenophialia ) that produces ergot alkaloids, a class of mycotoxins that aid the plant in establishment and drought tolerance but is the causative agent for fescue toxicosis when ingested in livestock [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Fescue toxicosis is a syndrome that includes vasoconstriction, high body temperature, low heart rate, increased blood pressure, low serum prolactin, agalactia, reduced forage intake, and poor weight gains observed in livestock grazing endophyte-infected, ergot alkaloid producing tall fescue [ 3 , 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For animals ingesting ergot alkaloids, a classic response is decreased serum prolactin concentrations [ 10 , 11 , 12 , 13 , 18 , 19 ] and vasoconstriction [ 3 , 5 , 8 ]. Ergot alkaloids are dopamine agonists that interact with DRD2 in a competitive manner [ 27 ] to alter serum prolactin [ 28 ] and vasoconstriction [ 5 , 6 , 7 , 8 ]. Campbell et al [ 29 ] identified a SNP in dopamine receptor D2 (DRD2) and established a relationship with serum prolactin concentrations in grazing steers and cows.…”
Section: Introductionmentioning
confidence: 99%
“…lolii and E. coenophiala, are commonly utilised in pasture-based agriculture as they enhance disease and insect pest control and thus improve pasture performance 3 6 . However, ergovaline has well documented effects on animal welfare, including poor weight gain from reduced feed intake, decreased fertility, and poor milk production 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Ergopeptides, such as ergotamine and ergovaline, are the most structurally complex ergot alkaloids, comprising D-lysergic acid linked via an amide bond to a three-membered peptide 7 . The alkaloids vary only in the composition of the peptide i.e.…”
Section: Introductionmentioning
confidence: 99%